Zoning of Groundwater Vulnerability to Seawater Intrusion Using Modified GALDIT Method in the Coastal Aquifer of Kendari Bay, Southeast Sulawesi - Fandy Irvansyah; Doni Prakasa Eka Putra; Wahyu Wilopo (Journal of Applied Geology, 2025)
Industrial expansion and the increasing use of groundwater in Kendari City have heightened the risk of water table decline and seawater intrusion, particularly in areas adjacent to Kendari Bay. This study aims to assess and map the vulnerability to seawater intrusion in the Kendari Bay region using a modified GALDIT method, supported by field observations and hydrogeochemical analyses for validation. The results indicate that zones with very low to low vulnerability are predominantly located in the western part of the study area, which is characterized by higher topographic slopes. In contrast, areas with very high to high vulnerability are concentrated along the coastal zone, where elevations are relatively low and proximity to the shoreline increases exposure to seawater intrusion. Validation through field and chemical data confirmed the reliability of the vulnerability zoning, as wells situated in high-vulnerability zones consistently exhibited seawater intrusion signatures, whereas those in low-vulnerability zones showed typical freshwater characteristics.